HUBUNGAN FAKTOR INDIVIDU DAN LINGKUNGAN RUMAH DENGAN KEJADIAN MALARIA DI PUSKESMAS KOELODA KECAMATAN GOLEWA KABUPATEN NGADA PROVINSI NTT - Idrus, Masriadi; ., Getrudis (Kesehatan Masyarakat UIN Alauddin Makassar, 2014)
Malaria is infectious disease caused by parasite of plasmodium genus which is infected through the bites of female anopheles mosquitoes. Malaria is considered a disease related of environment sanitation and behavior causing someone to be ill. The aim of the research is to findout the relationship between the use of repellent, mosquito net, knowledge, mosquito brood sites, home distance from mosquito brood, and cattel cultivation and the occurrence of malaria. The research is a cross sectional study. The sampel were 128 patients consisting of 43 patients suffering from malaria and 83 patients not suffering from malaria. The results of chi-square analysis indicate that the use repellent (X2 arithmetic (20,115), p=0,000), the use of mosquito net (X2 arithmetic (20,908), p=0,000), knowledge (X2 arithmetic (33,885), p=0,000), mosquito brood sites (X2 arithmetic (10,928), p=0,001), home distance from mosquito brood (X2 arithmetic (34,872 ), p=0,000), and cattle cultivation (X2 arithmetic (11,488), p=0,001) have a significant relationship with the occurrence of malaria. Thus, it is suggested to maintain einvironmental sanitation and prevent the behavior of having contact with mosquito.Keywords : individual and home environment, malaria